Implikasi Hak Cipta terhadap Distribusi dan Akses Buku Elektronik di Era Digital - Nurul Farida; Sri Rahayu (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
The world of knowledge and technology continues to develop rapidly, especially in the current digital era, which allows works that were previously in physical form to switch to digital form. This research aims to gain an understanding of the legal protection of copyrighted works in the digital era and the role of the government in dealing with the problem of copying copyrighted works. In this research, the juridical normative method is used; Copyright consists of moral and economic rights, and to use the economic rights of a work, the copyright holder must be permitted. Nevertheless, copyright laws need to be strengthened, especially to stop e-book piracy.